2008
DOI: 10.1038/onc.2008.360
|View full text |Cite
|
Sign up to set email alerts
|

A role for candidate tumor-suppressor gene TCEAL7 in the regulation of c-Myc activity, cyclin D1 levels and cellular transformation

Abstract: The pathophysiological mechanisms that drive the development and progression of epithelial ovarian cancer remain obscure. Recently, we identified TCEAL7 as a transcriptional regulatory protein often downregulated in epithelial ovarian cancer. However, the biological significance of such downregulation in cancer is not currently known. Here, we show that TCEAL7 is downregulated frequently in many human cancers and that in immortalized human ovarian epithelial cells this event promotes anchorageindependent cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 29 publications
(33 reference statements)
4
62
0
1
Order By: Relevance
“…Immunoblot analysis showed that there was a complete loss of TCEAL7 expression in several clonal lines when compared with vector clones (Chien et al, 2008). shRNA-stable clones (C4-2 and C4-4), which showed significant downregulation of TCEAL7 expression compared with vectortransduced clones (V1 and V3) ( Figure 1a) by real-time PCR, were chosen for further analysis.…”
Section: Tceal7 Negatively Regulates Nf-kb Pathwaymentioning
confidence: 99%
See 4 more Smart Citations
“…Immunoblot analysis showed that there was a complete loss of TCEAL7 expression in several clonal lines when compared with vector clones (Chien et al, 2008). shRNA-stable clones (C4-2 and C4-4), which showed significant downregulation of TCEAL7 expression compared with vectortransduced clones (V1 and V3) ( Figure 1a) by real-time PCR, were chosen for further analysis.…”
Section: Tceal7 Negatively Regulates Nf-kb Pathwaymentioning
confidence: 99%
“…TCEAL7 negatively regulates NF-jB pathway R Rattan et al Our previous analysis of protein/DNA binding assay for 54 transcription factors, using nuclear lysates from OSEtsT/hTERT clonal lines with TCEAL7 (control shRNA vector, V1) or without TCEAL7 (TCEAL shRNA clone, C4-2) (Chien et al, 2008), identified several transcription factors modulated by loss of TCEAL7 including NF-kB, which showed an approximately twofold increase in NF-kB binding to its target sequence in TCEAL7 in C4-2 clone compared with clone V1 (Figure 1b).…”
Section: Tceal7 Negatively Regulates Nf-kb Pathwaymentioning
confidence: 99%
See 3 more Smart Citations